Using sound-taste correspondences to enhance the subjective value of tasting experiences - Reinoso Carvalho, Felipe; Van Ee, Raymond; Rychtarikova, Monika; Touhafi, Abdellah; Steenhaut, Kris; Persoone, Dominique; Spence, Charles (Frontiers in Psychology, 2015)
The soundscapes of those places where we eat and drink can influence our perception of taste. Here, we investigated whether contextual sound would enhance the subjective value of a tasting experience. The customers in a chocolate shop were invited to take part in an experiment in which they had to evaluate a chocolate’s taste while listening to an auditory stimulus. Four different conditions were presented in a between-participants design. Envisioning a more ecological approach, a pre-recorded piece of popular music and the shop’s own soundscape were used as the sonic stimuli. The results revealed that not only did the customers report having a significantly better tasting experience when the sounds were presented as part of the food’s identity, but they were also willing to pay significantly more for the experience. The method outlined here paves a new approach to dealing with the design of multisensory tasting experiences, and gastronomic situations.